The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31234/osf.io/pqtgf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Did Students Learn Less During the COVID-19 Pandemic? Reading and Mathematics Competencies Before and After the First Pandemic Wave

Abstract: The first wave of the COVID-19 pandemic disrupted regular classes in spring 2020. Temporary school closures supposedly led to a considerable learning loss, particularly for low-achieving students. Schools in Baden-Württemberg, Germany, were closed for two months. Although distance learning was implemented, students spent less time learning. Additionally, teachers were faced with organizational and technological challenges of remote learning environments. The present study investigates the competencies of fifth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 15 publications
1
76
1
5
Order By: Relevance
“…Gore et al (2021) found Year 3 students studying math in low ICSEA schools (Index of Community Socio-Educational Advantage schools) to be two months behind the progress students made in 2019 in Australia. Lastly, Schult et al (2021) find learning losses of 0.07 SD in reading comprehension, 0.09 in operations, and 0.03 in numbers for Grade 5 students in Germany.…”
Section: Sample Sizementioning
confidence: 81%
See 2 more Smart Citations
“…Gore et al (2021) found Year 3 students studying math in low ICSEA schools (Index of Community Socio-Educational Advantage schools) to be two months behind the progress students made in 2019 in Australia. Lastly, Schult et al (2021) find learning losses of 0.07 SD in reading comprehension, 0.09 in operations, and 0.03 in numbers for Grade 5 students in Germany.…”
Section: Sample Sizementioning
confidence: 81%
“…Gore et al (2021) found the only losses to be amongst students from low ICSEA schools where the lower the ICSEA level the lower the educational advantage attending students have due to their parents' occupation and education, their geographical location, and the school's proportion of indigenous students (Australian Curriculum, Assessment and Reporting Authority, 2016). Schult et al (2021) found losses in math amongst grade 5 students to be more severe in low achieving students. In reading comprehension Schult et al (2021) found more severe losses amongst middle to high achieving students.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…One study reported an interaction between grade and SES, that is, for younger children from schools with low school-level SES, learning losses of 0.16 SD were found, while younger children from schools with medium school-level SES experienced learning gains of 0.15 SD (Gore et al, 2021). Additionally, low-performing students were more affected by COVID-19-related school closures in mathematics, while highperforming students were more affected by COVID-19-related school closures in reading (Schult et al, 2021). Finally, low-performing students benefited more from systematic online learning methods (Clark et al, 2020;Spitzer & Musslick, 2021).…”
Section: Differential Effects On Groups Of Studentsmentioning
confidence: 97%
“…For mathematics, effects varied between +0.20 SD and -0.19 SD (Mdn = -0.12 SD), with seven studies reporting a negative effect (Clark et al, 2020;Depping et al, 2021;Engzell et al, 2021;Maldonado & De Witte, 2020;Schult et al, 2021;Tomasik et al, 2020) and three studies reporting a positive effect (Gore et al, 2021;Meeter, 2021;Spitzer & Musslick, 2020) of COVID-19-related school closures on student achievement in mathematics. For reading, the effects found varied between -0.29 SD and +0.04 SD (Mdn = -0.14 SD), with six studies reporting a negative effect (Clark et al, 2020;Depping et al, 2021;Engzell et al, 2021;Maldonado & De Witte, 2020;Schult et al, 2021;Tomasik et al, 2020) and one study reporting a positive effect (Gore et al, 2021) of COVID-19-related school closures on student achievement in reading. For French as a foreign language, one study reported a large learning loss of 0.30 SD (Maldonado & De Witte, 2020), while another study reported an increase in correct solutions within a French learning program (van der Velde et al, 2021) during the COVID-19-related school closures.…”
Section: General Effects Of Covid-19-related School Closures On Student Achievementmentioning
confidence: 99%